GH Supplementation Effects on Cardiovascular Risk in GH Deficient Adult Patients: A Systematic Review and Meta-analysis - Giagulli, Vito A.; Castellana, Marco; Perrone, Raffaella; Guastamacchia, Edoardo; Iacoviello, Massimo; Triggiani, Vincenzo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2017)
Background and Objective: The current meta-analysis aims at evaluating whether the existing clinical evidence may ascertain the effects of growth hormone (GH) replacement therapy on cardiovascular risk, both in isolated GH deficiency (GHD) and in compensated panhypopituitarism including GH deficit. Methods: Original articles published from 1991 to 2015 were searched on Medline (Pubmed). Among an overall number of 181 potentially suitable studies, 24 fulfilled the selection criteria and were included in the analysis. Data aggregation was carried out through the calculation of the absolute risk reduction. The meta-analysis was then conducted by means of a fixed-effects model, according to the heterogeneity test (Chi-square statistic). Results: Fat-free mass (FFM) increase and fat mass (FM) reduction were found, together with a C-LDL reduction, a wide variation in glycaemia and a neutral effect on glycated haemoglobin (HbA1c) and blood pressure. These effects were valid both for isolated GHD patients and for those with compensated panhypopituitarism. The global outcome D showed a nonsignificant reduction of the overall cardiovascular risk (0.53; 95% C.I. -1.23, 2.85). Conclusion: Our meta-analysis shows no signnificatly positive trend in cardiovascular risk after both short and long-term GH supplementation therapy in adult GHD patients. However, a reduction of LDL cholesterol levels has been found. No differences were found between isolated GHD participants and those affected by panhypopituitarism well compensated since at least 3 months.
Keywords: panhypopituitarism